2020
DOI: 10.3390/cells10010020
|View full text |Cite
|
Sign up to set email alerts
|

Update on Prostate Cancer Diagnosis, Prognosis, and Prediction to Response to Therapy

Abstract: The wide range of novelties reported in this Special Issue of the journal Cells on prostate cancer (PCa) diagnosis, prognosis, and prediction to response to therapy, has led us to a series of considerations related to a better understanding of the current and future role of effective molecular biomarkers in individual patients with PCa [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…However, it is worth mentioning a proposal made in the late 1990s in an invited lecture at the Milan (Italy) National Cancer Institute, in a seminar organized by the late Dr Juan Rosai. The proposal was in favor of a classification of the preinvasive lesions of the prostate based on an approach similar to that in the breast and taking into consideration what was reported in the 1987 Dr Bostwick’s publication of the concept of “Grade 3, representing carcinoma in situ”: 1 low nuclear grade (ie, LGPIN), intermediate nuclear grade (ie, HGPIN) and high nuclear grade (ie, IDC-P). The comment made by Dr Rosai was a laconic one as if not endorsing it.…”
Section: The Real Beginning Of Our Experience With Prostate Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth mentioning a proposal made in the late 1990s in an invited lecture at the Milan (Italy) National Cancer Institute, in a seminar organized by the late Dr Juan Rosai. The proposal was in favor of a classification of the preinvasive lesions of the prostate based on an approach similar to that in the breast and taking into consideration what was reported in the 1987 Dr Bostwick’s publication of the concept of “Grade 3, representing carcinoma in situ”: 1 low nuclear grade (ie, LGPIN), intermediate nuclear grade (ie, HGPIN) and high nuclear grade (ie, IDC-P). The comment made by Dr Rosai was a laconic one as if not endorsing it.…”
Section: The Real Beginning Of Our Experience With Prostate Neoplasmsmentioning
confidence: 99%
“…Such specimens have allowed us to acquire deep knowledge of the morphology of the lesions and of their spectrum and, above all, of their clinical significance. This was always coupled with an active research activity 1 …”
mentioning
confidence: 99%
“…Today, the healthcare system has benefited greatly from a number of advantages of artificial intelligence (AI)‐based strategies, such as the chance of storing, comparing, and classifying enormous data via high‐speed computers, and all these fashions have been precisely implemented into the fields of drug delivery, medicine, and cancer research (treatment, imaging, and cell sorting). [ 178–183 ] In particular, machine learning (ML)—an application of AI—enables automatically learning of the trained datasets without any internal programming. The attribution of recognizing and analyzing patterns employed in biomedical and clinical areas creates an enormous level of heterogeneous data.…”
Section: Artificial Intelligence Of Cell Isolation and Characterizationmentioning
confidence: 99%
“…Prostate cancer (PCa) is the most commonly diagnosed cancer and the second leading cause of cancer‐related death among men 1,2 . Appropriate treatment requires accurate prognostic prediction 3 . However, numerous studies have demonstrated that currently used prognostic indicators, including prostate‐specific antigen (PSA) level, clinical stage and Gleason grade, inadequately predict the prognosis of PCa patients, particularly men with clinically localized disease 4–6 .…”
Section: Introductionmentioning
confidence: 99%